Integration of ICT with traditional methods in English Classes (Journal of Pedagogical Inventions and Practices, 2022)
The article is devoted to the study of the implementation of ICT into English teaching/learning process. The paper analyzes the need to introduce modern informative technologies into the traditional educational process and identifies the main positive opportunities for using innovative technologies in the education system.